PENGARUH BESARAN DAN JUMLAH KASUS BANJIR UNTUK HITUNGAN HIDROGRAF SATUAN TERHADAP KETELITIAN BANJIR RANCANGAN - , REVIANTI COENRAAD, ST. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Design discharge is important hydrological information for planning various hydraulic structures. Various methods can be used to predict design discharge, such as unit hydrograph theory. Under this theory, transforming rainfall to design discharge can be done simply and easily without studying the complex characteristics of watershed. Problem to be coped with is the number of flood case required to derive the unit hydrograph for obtaining a unit hydrograph that represents a watershed and to obtain accurateness of certain design discharge. Subject of this study is based on four watersheds, two in the Province of Daerah Istimewa Yogyakarta: Code and Gajahwong watersheds, and two in the Province of Jawa Tengah: Upstream Progo and Bogowonto watersheds. Collins method is used to derive hydrograph for every selected flood case. Unit hydrograph representing a watershed is obtained by averaging the results of unit hydrograph analysis on several flood cases occurs in the studied watershed, in which this study uses the unit hydrograph. Accuracy analysis of unit hydrograph is carried out by comparing design discharge resulted from used unit hydrograph application and referred design discharge reference, which is the discharge of used unit hydrograph result on the most flood cases and analysis result of measured maximum discharge frequency. Based on the analysis, the one with the smallest relative error is assumed as the most accurate. Results of this study show a tendency that larger number of flood cases used to derive the unit hydrograph implies smaller peak of the resulted unit hydrograph and more accurate designed discharge calculation. To obtain less than 10% relative error on the designed discharge for the outmost numbers of flood cases, it requires at least 10 flood cases with spesific discharge between 0.40 to 1.10 m 3 /s/km 2 . Designed discharge resulted from unit hydrograph indicates over estimated as well as under estimated tendency for various period to maximum discharge of the frequency analysis with relatively short length of data (<10 years).